Construction of three-dimensional vascularized functional human liver tissue using a layer-by-layer cell coating technique. (July 2017) - Sasaki, Kazuki; Akagi, Takami; Asaoka, Tadafumi; Eguchi, Hidetoshi; Fukuda, Yasunari; Iwagami, Yoshifumi; Yamada, Daisaku; Noda, Takehiro; Wada, Hiroshi; Gotoh, Kunihito; Kawamoto, Koichi; Doki, Yuichiro; et al.
Abstract: The creation of artificial liver tissue is an active area of research due to the shortage of donors for liver transplantation. Here we investigated whether a simple and efficient cell coating technique developed in our laboratory could be used to generate functional vascularized liver tissue. This technique creates three-dimensional tissue by loading cells sterically onto other cells that have been coated with layer-by-layer (LbL) nanofilms of fibronectin and gelatin, two extracellular matrix proteins. We used this technique to construct homogenous, dense, well-vascularized liver tissue from cryopreserved human primary hepatocytes, human umbilical vein endothelial cells, and normal human dermal fibroblasts. Using LbL cell coating technique resulted in higher cellular function in terms of human albumin production ( P  < 0.01) and cytochrome P450 activity ( P  < 0.01) in vitro. Furthermore, after being transplanted subcutaneously into NOD/SCID mice, the vascularized liver tissue showed greater albumin production in the early stage than non-vascularized tissue or a hepatocyte suspension ( P  < 0.01). Histological examination demonstrated that compare to non-vascularized tissue, there were many less-morphologically changed and intact hepatocytes in the vascularized tissue. This cell coating technique would be applicable to the generation of vascularized functional liver tissue for regenerative medicine in the future. Highlights: The layer-by-layer technique coated cells with fibronectin and gelatin. Well-vascularized liver tissue was constructed using a cell coating technique. The resulting liver tissue had high albumin production and CYP activity in vitro. The liver tissue also produced albumin in vivo after transplantation into mice.